Exploiting in silico structural analysis to introduce emerging genotype–phenotype correlations in DHCR24-related sterol biosynthesis disorder: a case study - Cocciadiferro, Dario; Mazza, Tommaso; Vecchio, Davide; Biagini, Tommaso; Petrizzelli, Francesco; Agolini, Emanuele; Villani, Andrea; Minervino, Daniele; Martinelli, Diego; Rizzo, Cristiano; Boenzi, Sara; Panfili, Filippo Maria; et al. (Frontiers in Genetics, 2024)
Desmosterolosis is a rare sterol biosynthesis disorder characterized by multiple congenital anomalies, failure to thrive, severe developmental delay, progressive epileptic encephalopathy, and elevated levels of desmosterol caused by biallelic mutations of DHCR24 encoding 3-βhydroxysterol Δ-24-reductase. DHCR24 is regarded as the key enzyme of cholesterol synthesis in the metabolism of brain cholesterol, as it catalyzes the reduction of the Δ-24 double bond of sterol intermediates during cholesterol biosynthesis. To date, fifteen DHCR24 variants, detected in 2 related and 14 unrelated patients, have been associated with the desmosterolosis disorder. Here, we describe a proband harboring the never described DHCR24 homozygous missense variant NM_014762.4:c.506T>C, NP_055577.1:p.M169T, whose functional validation was confirmed through biochemical assay. By using molecular dynamics simulation techniques, we investigated the impact of this variant on the protein stability and interaction network with the FAD cofactor, thereby providing a preliminary assessment of its mechanistic role in comparison to all known pathogenic variants, the wild-type protein, and a known benign DHCR24 variant. This report expands the clinical and molecular spectrum of the DHCR24related disorder, reports on a novel DHCR24 deleterious variant associated with desmosterolosis and gives new insights into genotype-phenotype correlations.